DAMPAK BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP PENGAMBILAN KEPUTUSAN MANAJERIAL DALAM MENINGKATKAN KINERJA PERUSAHAAN - Rini Wijaya Ningsih; Anggraini Putri Otorus Carolina, Diana Prameswari, Maya Tika Zulkarnain, Naura Salsabilla, Nico Chri (JOURNAL OF COMMUNITY DEDICATION, 2023)
Leadership and organizational culture are two key elements that influence managerial decision making and business performance. This article discusses how leadership style and organizational culture influence decision making and how it affects company performance. Effective leadership and an adaptable organizational culture have proven critical in driving better decision making, which improves company performance, according to empirical research and literature reviews. This paper also discusses managers' day-to-day responsibilities in creating a culture and leadership that facilitate wise strategic choices.